Printing conductive ink tracks on textile materials - Tan, Siun Cheng (2015)
Textile materials with integrated electrical features are capable of creating intelligent articles with wide range of applications such as sports, work wear, health care, safety and others. Traditionally the techniques used to create conductive textiles are conductive fibers, treated conductive fibers, conductive woven fabrics and conductive ink. The technologies to print conductive ink on textile materials are still under progress of development thus this study is to investigate the feasibility of printing conductive ink using manual, silk screen printing and on-shelf modified ink jet printer. In this study, the two points probe resistance test (IV Resistance Test) is employed to measure the resistance for all substrates. The surface finish and the thickness of the conductive inks track were measured using the optical microscope. The functionality of the electronics structure printed was tested by introducing strain via bending test to determine its performance in changing resistance when bent. It was found that the resistance obtained from manual method and single layer conductive ink track by silkscreen process were as expected. But this is a different case for the double layer conductive ink tracks by silkscreen where the resistance acquired shows a satisfactory result as expected. A micro-structure analysis shows the surface finish for the single layer conductive inks tracks were not good enough compared to the double conductive ink track. Furthermore, the bending tests provide expected result if increasing of the bend angle will decrease the level of conductivity. The silver conductive paint RS186-3600 could provide low resistance which was below 40 ohm after printed on fabrics material.